Optimizing Investment Strategies to Improve the Welfare of Migrant Workers - Merlinda, Santi; Inayati Nuraini Dwi Putri; Sri Handayani; Fajar Firmasnyah; Syarifah Jamilah (Pascasarjana Universitas Mataram, 2025)
The high public interest in becoming migrant workers is motivated by the narrowing number of available jobs and the low wages of domestic workers. This is the reason why migrant workers dare to take the risk to leave their home country and work abroad. However, migrant workers often find challenges and obstacles in financial management of their income while abroad. The financial management constraints faced by migrant workers are triggered by the low level of financial literacy, so a training program related to financial literacy is needed as an effort to improve financial management skills for migrant workers. This service program focuses on investment strategies for the welfare of migrant workers. This program aims to broaden the insights and knowledge of migrant workers regarding the correct investment strategy as an effort to achieve economic independence. The training method carried out in this service program is based on interactive training related to appropriate investment strategies. The results of this study are expected to improve the financial literacy of migrant workers, especially in the context of investing, so that it can be used as a provision for migrant workers to improve their economy sustainably in the long term.